Quality of Cultured Wader Pari During Storage at Different Temperature - Almira Islamei Pratiwi; Amir Husni; Siti Ari Budhiyanti; Bambang Retno Aji (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Rasbora lateristriata is one Indonesian freshwater fish consumed by society as a source of animal protein. Like fish in general, rasbora is considered as perishable food, so it is necessary to apply a proper storage technique, one of which is cold storage. The purpose of this study was to determine the proper storage temperature of the rasbora in the storage of freezer, chiller and ice. The raw materials used was rasbora in size of 2 grams/fish. The Wader was caught then pondered (2,1 kg). Rasbora was split into three different storages those were freezer (-20°C), chiller (4°C), and ice (10°C). The study design used a completely randomized design with storage temperature factors and the duration of storage with three treatments and three replications. Observations were made on days 0, 5, 10, 15, 20, 25, and 30 include TPC test, TVB, pH and organoleptic. The results showed that treatment of freezer, chiller, and ice storage were able to inhibit decay until the 40th day, 13th day, and day 2, repectivelly. Thus, the freezer storage (-20° C) provides more effective in inhibiting decay by TPC, TVB, pH and organoleptic.